2000
DOI: 10.1177/1359104500005002009
|View full text |Cite
|
Sign up to set email alerts
|

Functional Visual Loss in Childhood and Suggestibility

Abstract: A B S T R A C T Visual disturbance in which no organic ophthalmological or neurological abnormalities are found is referred to as functional (or psychogenic) visual loss. Based on our preliminary results on this disorder, we set out to examine whether the individual's suggestibility and the effect of suggestion play a major role in its etiology and course; specifically, whether the age trend of suggestibility is reflected in the age distribution of this disorder and whether a non-damaging physical trauma of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A study of 10 patients used transcranial magnetic stimulation with improvement in 9 patients [23]. A case series of 33 paediatric patients reported that 28 recovered with suggestion therapy [24]. The Edinburgh FND research group published a detailed description of the more multi-faceted approach, describing visual recovery in two individuals with complete functional visual loss, with a focus on explanatory models, combined with transcranial magnetic stimulation and hypnotherapy [25].…”
Section: Further Managementmentioning
confidence: 99%
“…A study of 10 patients used transcranial magnetic stimulation with improvement in 9 patients [23]. A case series of 33 paediatric patients reported that 28 recovered with suggestion therapy [24]. The Edinburgh FND research group published a detailed description of the more multi-faceted approach, describing visual recovery in two individuals with complete functional visual loss, with a focus on explanatory models, combined with transcranial magnetic stimulation and hypnotherapy [25].…”
Section: Further Managementmentioning
confidence: 99%
“…Abe and Suzuki (2000) found that suggestion therapy was effective for treatment of functional visual loss in children and adolescents between 6 and 16 years of age. For example, the nature and rate of her reacquisition of verbal understanding was hypothesised by the clinician and JP responded predictably.…”
Section: Influence Of Suggestibility and Hypothesisingmentioning
confidence: 99%
“…A time frame for recovery was also provided and JP regained full hearing within this time. Abe and Suzuki (2000) found that suggestion therapy was effective for treatment of functional visual loss in children and adolescents between 6 and 16 years of age. Suggestion and hypothesising are more likely to be useful tools in therapy when there is good engagement.…”
Section: Influence Of Suggestibility and Hypothesisingmentioning
confidence: 99%